대전 지역 여대생의 유제품 섭취와 관련된 사회심리적 요인 - 신은미(Eun Mi Shin); 김경원(Kyung Won Kim) (Korean journal of community nutrition, 2003)
The purpose of this study was to investigate the psychosocial factors influencing dairy product consumption of female university students in Daejeon. The Theory of Planned Behavior provided the basis for this study. As a result of the pilot-study, 18 behavioral beliefs, 8 normative beliefs, and 12 control beliefs were identified. The subjects (n=236) were grouped into a high-consumption group (1 serving/day, n=117) and a low consumption group (< 1 serving/day, n=119). The data were analyzed using t-tests or $χ$$^2$-tests. Among the general characteristics, there were significant differences in the amount of pocket money spent per month, residence type (p<0.01), weight, frequency of exercise and perceived health status (p<0.05) of the subjects. With respect to the 18 behavioral beliefs, the high consumption group responded less negatively on ‘eating dairy foods would not be convenient’ than the low consumption group (p<0.05). None of the subjective normative items were significantly different between the two groups. However, notable differences were found in regard to the control beliefs (8 out of 12 control beliefs). These included overall control over consuming dairy products (p< 0.001), as well as specific beliefs regarding barriers such as easy spoilage of dairy products, the cost, eating them for snacks and dislike for them (p<0.05). In addition, specific situations, such as ‘when I want them I get them’ (p<0.01), eating out and the availability of dairy foods at home (p<0.05) were significantly different between the two groups. The high consumption group showed more control over these barriers or situations. These results suggest that nutritional education for young female adults should incorporate strategies to increase their perceived control over the consumption of dairy products by removing barriers and including environmental approaches which address the availability issues.